2018
DOI: 10.1002/qua.25651
|View full text |Cite
|
Sign up to set email alerts
|

Transmission channels in the time‐energy uncertainty relation approach to molecular conductance: Symmetry rules for the electron transport in molecules

Abstract: The concept of transmission channel plays a key role in the theory of molecular conductors. They are usually constructed from one-electron functions (molecular spin orbitals) in the extensively employed LCAO-MO method. Thus, the electric conductance can be obtained from the transmission matrix, whose diagonalization leads to a set of transmission eigenchannels. In this work, it is shown how using the time-energy uncertainty relation approach, the electron transport can be also analysed in terms of coupled tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…Batra 35,36 derived the expression of G 0 by applying the uncertainty relation to the case of a free electron crossing a monodimensional conductor under the action of a nite bias voltage, DV. Recently, a generalization to interacting electrons subjected to the external potential created by the nuclei in a molecule was proposed, 34 giving rise to the following expression,…”
Section: Molecular Electric Conductance From Electron Deformation Orbmentioning
confidence: 99%
See 2 more Smart Citations
“…Batra 35,36 derived the expression of G 0 by applying the uncertainty relation to the case of a free electron crossing a monodimensional conductor under the action of a nite bias voltage, DV. Recently, a generalization to interacting electrons subjected to the external potential created by the nuclei in a molecule was proposed, 34 giving rise to the following expression,…”
Section: Molecular Electric Conductance From Electron Deformation Orbmentioning
confidence: 99%
“…For instance, the amount of electrons promoted from valence to conduction bands upon the electric perturbation can be obtained, 14 and simple orbital symmetry rules for the formation of transmission channels can be inferred. 34 Another appealing feature of using EDOs is that electron and hole densities associated to a given transmission channel can be represented in real space. This provides, as will be shown in the next section, a visual tool to understand the conducting/ insulating character of molecular wires by means of the electron and hole density distributions along the transport region.…”
Section: Molecular Electric Conductance From Electron Deformation Orbmentioning
confidence: 99%
See 1 more Smart Citation
“…These channels provide both qualitative and quantitative mechanism of charge flow through the molecular conductor. [50] It is found that EDOs pair off, displaying the same eigenvalue but opposite sign, where each pair represents the magnitude of accumulation/depletion of charge at different molecular regions. n def , as total charge displacement can be found as summation over positive eigenvalues of deformation density matrix, equation 3.…”
Section: Methodsmentioning
confidence: 96%
“…EDO concept has been also used in the construction and molecular expression of transmission channels which plays a crucial role in molecular‐level conduction and can be found by diagonalization of transmission matrix as eigenchannels. These channels provide both qualitative and quantitative mechanism of charge flow through the molecular conductor …”
Section: Methodsmentioning
confidence: 99%